Analisis Kualitatif terhadap Kemampuan Berpikir Reflektif Peserta Didik pada Pembelajaran IPA Kelas IV Sekolah Dasar: kemampuan berpikir reflektif - hidayati, fitria; Kurniasari, Kurniasari; Kastur, Annita; Julianto, Julianto; Rahmawati, Endah (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2025)
In today’s learning context, the ability of students to think reflectively is a crucial concern because it influences their understanding of scientific concepts. However, reflective indicators related to independent exploration and direct experience are still low. Data show that only 31.25% of students independently seek information, and just 9.4% prefer learning through experiments, indicating that practical approaches are not yet fully embedded in learning habits. Furthermore, only 40% of students can connect personal experiences with the concepts being studied. On the other hand, students already demonstrate a positive attitude toward science learning, as seen in their awareness of its importance and their willingness to ask questions when facing difficulties. Strengthening independent and experience-based learning strategies is therefore essential to support success in science learning. This study aims to analyze the reflective thinking abilities of fourth-grade elementary school students in science using a case study approach with qualitative analysis. Data were collected through observation, interviews, and document analysis. The findings are expected to provide educators with insights into developing learning methods that can better foster students’ reflective thinking skills.